A rendezvous block‐based authentication framework for service‐level security in decentralized cloud resources. Issue 4 (9th August 2022) - Murugaiyan, Pajany; Godandapani, Zayaraz
Abstract: Cloud services are distributed from manifold sources with autonomous security procedures. The conventional authentication methods result in asynchronous security towards multi‐resource access and sharing. This provides volatile authentication for sequential service sessions. For alleviating this issue, a Rendezvous Block‐based Authentication Framework (RBAF) is proposed. This framework is backboned with a blockchain paradigm that differentiates authentication based on rendezvous and asynchronous attributes. The modifications in initial and final attributes are observed, intended for training, and supplanted with service‐dependent authentications. In the different sessions, attribute‐based authentication and agreed end‐to‐end security are administered using agreed keys that are valid within the sessions. This key generation is modified using the new session and user attributes based on learning recommendations. The ledger paradigm records the session and its associated attributes for different training instances, based on which service flexibility is ensured. The proposed framework's performance is verified using the metrics service distribution ratio, false rate, session uptime, and service delay.